Antidiabetic and Antioxidant Potentials of Amaranthus hybridus in Streptozotocin-Induced Diabetic Rats. (4th July 2017) - Balasubramanian, T.; Karthikeyan, M.; Muhammed Anees, K. P.; Kadeeja, C. P.; Jaseela, K.
ABSTRACT: Context: Amaranthus hybridus (Amaranthaceae) has been used as a folk medicine in southern parts of India for the treatment of diabetes. Objective : This research evaluates the antidiabetic and antioxidant effects of Amaranthus hybridus ethanol leaf extract (AHELE) in streptozotocin-induced diabetic rats. Methods : Blood glucose levels of diabetic rats were measured on days 1, 4, 7, and 15 after oral administration of AHELE at doses of 200 and 400 mg/kg for 14 days. The effects of extract were observed on serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, serum alkaline phosphatase, cholesterol, high- and low-density lipoprotein, antioxidant potential, and histopathological changes. Result : AHELE (200 and 400 mg/kg) caused a significant ( p < 0.001) reduction in blood glucose levels on day 15 (152.2 and 181.2 mg/dL, respectively versus diabetic control 287.0 mg/dL). The extract also improved serum biochemical parameters associated with diabetes. A significant ( p < 0.001) decrease in malondialdehyde protein (liver: 15.92, 12.29 nmol/mg, and kidney: 13.92, 10.29 nmol/mg vs. diabetic control 25.49, 24.49 nmol/mg), increase in superoxide dismutase protein (14.01; 17.47 IU/mg, and 25.01; 37.47 IU/mg vs. diabetic control 9.65; 15.65 IU/mg), catalase protein (35.80, 44.49, and 39.80, 49.69 nmol/min/mg vs. diabetic control 18.45, 20.85 nmol/min/mg) and reduced glutathione protein (44.77, 55.08 and 40.77, 51.08 μM/gm vs. diabetic control 29.81, 26.50 μM/gm) were observed. Conclusions : The study reveals that treatment of diabetic rats with AHELE significantly reduced hyperglycemia-associated oxidative damage. This could provide a rationale for the use of the plant to treat diabetes in folk medicine.